1996
DOI: 10.1038/380646a0
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of ribonucleoprotein interaction determined by RNA folding during complex formation

Abstract: Many proteins involved in pre-mRNA processing contain one or more copies of a 70-90-amino-acid alphabeta module called the ribonucleoprotein domain. RNA maturation depends on the specific recognition by ribonucleoproteins of RNA elements within pre-mRNAs and small nuclear RNAs. The human U1A protein binds an RNA hairpin during splicing, and regulates its own expression by binding an internal loop in the 3'-untranslated region of its pre-mRNA, preventing polyadenylation. Here we report the nuclear magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
262
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(275 citation statements)
references
References 27 publications
10
262
0
1
Order By: Relevance
“…Structural studies revealed that the ability of the helix to bend at the bulged nucleotides is critical for protein binding. The RRM-containing U1A protein binds to the U1 snRNA and to its own pre-mRNA (Oubridge et al 1994;Allain et al 1996) by recognizing 6 unpaired nucleotides in a sequence-specific manner (Hall 1994). The high sequence conservation of the bulged nucleotides of the TLC1 RNA bulged stem and the importance of an intact stem suggest that Est1p could recognize this structure, at least in part, in a similar manner.…”
Section: How Might Est1p Interact With the Bulged Stem?mentioning
confidence: 98%
“…Structural studies revealed that the ability of the helix to bend at the bulged nucleotides is critical for protein binding. The RRM-containing U1A protein binds to the U1 snRNA and to its own pre-mRNA (Oubridge et al 1994;Allain et al 1996) by recognizing 6 unpaired nucleotides in a sequence-specific manner (Hall 1994). The high sequence conservation of the bulged nucleotides of the TLC1 RNA bulged stem and the importance of an intact stem suggest that Est1p could recognize this structure, at least in part, in a similar manner.…”
Section: How Might Est1p Interact With the Bulged Stem?mentioning
confidence: 98%
“…However, it was later shown that RRMs can contain supplementary secondary structures that are important for proper folding or RNA binding. For example, the structure of the U1A RRM in complex with RNA showed that this domain possesses an additional helix α 3 at its C-terminus that interacts with the β-sheet surface of the RRM in its free form but rotates away from the β-sheet when the RRM is in complex with RNA [2]. Although this helix is not directly involved in RNA binding, it was…”
Section: Protein Productionmentioning
confidence: 99%
“…Many RNA binding proteins have been purified using a combination of ion exchange chromatography and size-exclusion chromatography [2,12,18,22,36,46].…”
Section: Purification Of Rna Binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The U1A protein tertiary structure has been obtained in solution in complex with one of its specific RNA, the PIE from its pre-mRNA [19,42]. The determinants for binding have been analyzed in detail and compared with those of the previously known crystal complex with stem-loop II from U1-snRNA [43].…”
Section: Binding Specificity Of U1amentioning
confidence: 99%